2002
DOI: 10.1111/j.1574-6941.2002.tb01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong, weak, and missing links in a microbial community of the N.W. Mediterranean Sea

Abstract: Planktonic microbial communities often appear stable over periods of days and thus tight links are assumed to exist between different functional groups (i.e. producers and consumers). We examined these links by characterizing short-term temporal correspondences in the concentrations and activities of microbial groups sampled from 1 m depth, at a coastal site of the N.W. Mediterranean Sea, in September 2001 every 3 h for 3 days. We estimated the abundance and activity rates of the autotrophic prokaryote Synecho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 69 publications
5
48
0
2
Order By: Relevance
“…Diel dynamics in VP were detectable although not pronounced (Table 1), probably due to the low diel dynamics in bacterial activity in the North Sea (Winter et al, 2004). More pronounced diel patterns in bacterioplankton production have been reported for oligotrophic systems such as the Mediterranean Sea (Bettarel et al, 2002). The short-term variability observed in the viral infection cycle in the coastal North Sea as the presence and absence of distinct bands in the newly produced viral populations was evident on a time scale of days ( Figure 5).…”
Section: Dynamics Of Newly Produced Viruses V Parada Et Almentioning
confidence: 95%
See 1 more Smart Citation
“…Diel dynamics in VP were detectable although not pronounced (Table 1), probably due to the low diel dynamics in bacterial activity in the North Sea (Winter et al, 2004). More pronounced diel patterns in bacterioplankton production have been reported for oligotrophic systems such as the Mediterranean Sea (Bettarel et al, 2002). The short-term variability observed in the viral infection cycle in the coastal North Sea as the presence and absence of distinct bands in the newly produced viral populations was evident on a time scale of days ( Figure 5).…”
Section: Dynamics Of Newly Produced Viruses V Parada Et Almentioning
confidence: 95%
“…Considering that the richness of bacteriophages in coastal surface waters is relatively high (Wommack et al, 1999b) and that the decay of viruses in surface waters is in the range of 1-2 days (Heldal and Bratbak, 1991;Wilhelm et al, 1998), a rapid succession of infection targets can be assumed and consequently, a tight control of bacterioplankton evenness by bacteriophages. These temporal dynamics in viral infection and phage production have been addressed only on short-time scales (Bettarel et al, 2002;Winter et al, 2004) but viral diversity was not analyzed thus far and is subject of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, our study assessed host and viral diversity simultaneously-samples that were discrete in both time and space. A further factor that may help to explain the lack of correlation is that in surface waters, viral turnover rates are variable, in the order of hours (Bettarel et al, 2002;Clokie et al, 2006) to a few days (Parada et al, 2008). For these reasons, it may be unreasonable to expect that a single snapshot will reveal infection dynamics.…”
Section: Cyanomyoviruses Environmental Conditions and Cyanobacterialmentioning
confidence: 99%
“…The studies disagree with each other as to when viral abundance reaches a maximum (Bettarel et al, 2002). One of the most comprehensive surveys of marine microbial communities was carried out by Bettarel who showed that natural viral abundance peaked at around 1800 h (Bettarel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%